Leprosy and lymphatic filariasis-related disability and psychosocial burden in northern Mozambique. - Robin van Wijk; Litos Raimundo; Domingos Nicala; Yuki Stakteas; Adelaide Cumbane; Humberto Muquingue; Julie Cliff; Wim van Brakel; Artur Manuel Muloliwa (Public Library of Science (PLoS), 2024)
Introduction Leprosy and lymphatic filariasis (LF) are among the most disabling neglected tropical diseases (NTDs) that affect the citizens of Mozambique, especially in the Northern provinces. The irreversible impairments caused by these NTDs often lead to psychosocial consequences, including poor mental wellbeing, stigma and reduced social participation. Limited data on these consequences are available for Mozambique, which are urgently needed to better understand the true disease burden and support advocacy for scaling up interventions. Methods A cross-sectional mixed-methods study was conducted. Mental distress was assessed with the Self Reporting Questionnaire (SRQ-20), participation restriction was assessed with the Participation Scale Short (PSS) and perceived stigma was assessed with the Explanatory Model Interview Catalogue affected persons stigma scale (EMIC-AP). Additionally, semi-structured interviews were conducted with persons affected by leprosy or LF. Results In total, 127 persons affected by leprosy and 184 persons affected by LF were included in the quantitative portion of the study. For the qualitative portion, eight semi-structured interviews were conducted. In both disease groups, mental distress was found in 70% of participants. Moreover, 80% of persons affected by leprosy and 90% of persons affected by LF perceived stigma. Moderate to extreme participation restriction was found in approximately 43% of persons affected by leprosy and in 26% of the persons affected by LF. Persons affected by leprosy and LF felt excluded from society and experienced financial problems. More severe disabilities were associated with more severe outcomes for mental wellbeing, participation restriction and stigma. By contrast, participation in a self-care group was suggested to have a positive impact on these outcomes. Conclusion The findings provide evidence that persons affected by leprosy and LF must not only confront physical impairments but also experience significant disability in the psychosocial domain, including mental distress, participation restriction and stigma. These challenges must be urgently addressed by NTD programmes to promote the inclusion and wellbeing of persons affected by NTDs.